The scientific-methodical place of the subject "Architectural ethnology of residential buildings" in the preparation of the specialty "architect" - Duisebai Есболат (Рroblems of engineering and professional education, 2023)
The article discusses the scientific foundations and the subject of study of the discipline "Architectural typology of residential, public buildings and structures". In the professional training of an architect, in the learning process, it occupies a central place and pays special attention to the study of the architectural typology of residential and public buildings and structures, as one of the main sections of modern architectural science. Architectural typology reveals social, urban planning, functional, constructive, economic and architectural and artistic requirements and parameters, creates a classification and nomenclature of types of residential buildings, establishes standards and composition of premises. Significant sections of the curriculum are devoted to the prospect of developing new types of residential buildings.